Apoplastic sucrose concentration is a key regulator of the diel course stomatal movements - Freire, Francisco Bruno Silva (2024)
Recent evidence suggests that sucrose is a molecule capable of inducing stomatal closure at high concentrations, in which the accumulation of sucrose in the apoplast would induce stomatal closure in periods of high photosynthetic rate and, thus, optimizing the efficiency of use of water in plants (WUE). However, it is unclear how this process contributes to the daily regulation of WUE and its relationship with the role of sucrose within guard cells (GC) during stomatal closure. Within this perspective, this project will test the hypothesis that sucrose is a key molecule that integrates photosynthesis and stomatal movements and that its levels present in the leaf apoplast correlate positively during opening and negatively during stomatal closure with the stomatal conductance (gs). First of all, an efficient method of leaf apoplast collection was established using methanol (MeOH) and water (ddH2O) as infiltration fluids for metabolic analysis via gas chromatography coupled to mass spectrometry using tobacco and Arabidopsis leaves. Subsequently, experiments were carried out to determine the dynamics of stomatal movements along with the metabolic profile of leaves and apoplast throughout the day using wild-type (NtWT) and transgenic tobacco plants with reduced expression of the sucrose transporter SUT1 in GC (NtSUT1), which has a lower capacity to import sucrose from the apoplast to the GC symplast. Multivariate analyzes were performed with gas exchange and metabolomics data as well as gs kinetics under different concentrations of sucrose, glucose and fructose. Finally, was determined the dynamics of the stomatal opening and the internal level of sugars in epidermal fragments subjected to 25 mM sucrose under light, along with their metabolic profile. The results of the apoplast collection method demonstrated that the MeOH increased the apoplast volume recovery yield, but also increased symplast contamination, mainly in Arabidopsis. When using MeOH as infiltration fluid, we recommend the calculation of a correction factor by using enzymatic activities to attest the apoplast purity. Due to the absence of differences in metabolic analyzes between both infiltration fluids, the use of ddH2O is the most recommended as it is easily accessible and non-toxic. Across the diel course of analyzes in NtWT and NtSUT1 plants, the stomatal opening and closure were associated with low and high apoplastic sucrose concentrations, respectively. Furthermore, due to the effect of exogenous application of sugars, the opening and closure rapidity were positively and negatively correlated with the sucrose concentration in illuminated leaves, respectively. Additionally, the sucrose-mediated stomatal response was significantly reduced in epidermal fragments of NtSUT1 plants. Taken together, our results indicate that sucrose is, in fact, a master regulator of gs, being capable of inducing stomatal opening and closure in a concentration and location dependent manner.